IMPACT OF MOTOR LEARNING BASED ON TEAM SPORTS IN DEVELOPING SPORTS SKILLS AMONG A SAMPLE OF CHILDREN AGED 8 TO 10 YEARS IN PRIMARY SCHOOL - T.A. Muhammad Hashem Baddai (Proximus Journal Publishing, 2025)
This study looks at how team sports-based motor learning affects the development of sports skills in elementary school students between the ages of 8 and 10. An experimental group that received motor training and played team sports, as well as a control group that did not receive the same instruction, were included in the study's quasi-experimental design. Forty youngsters were chosen at random to make up the sample. Tests measuring running speed, jump height, and throwing accuracy were used to evaluate sports skills both before and after the intervention. Following the training, the experimental group's post-test scores significantly improved as compared to their pre-test results, demonstrating observable improvements. These results demonstrate how well-suited training regimens are for this age range. The study highlights how crucial it is to modify educational curriculum to accommodate children's developmental needs. Each age stage is characterized by a natural development of some capabilities and can also develop these capabilities through training and practice. (Salih and Ahmed 2020, 13)
Keywords: Motor learning; team sports; sports skills